A Comparative Analysis of Ropivacaine- Fentanyl vs Bupivacaine-Fentanyl in Labour Analgesia - Vikas Aron; Kapil Lamba (Academia Anesthesiologica International, 2019)
Background: The pains of labor result in a maternal stress response, which is neither beneficial for the fetus nor the mother. The present study was conducted to compare ropivacaine- fentanyl vs Bupivacaine-Fentanyl in labour analgesia. Subjects and Methods: The present study was conducted on 48 females of ASA Grades I and II, who requested epidural labour analgesia. Patients were divided into two equal groups. Group I patients received 10?mL of bupivacaine 0.1% + fentanyl 20??g and group II patients received 10?mL of ropivacaine 0.1% + fentanyl 20??g. Fetal heart rate, blood pressure was monitored regularly. VAS scale was also assessed. Results: There was non- significant difference in MAP, MHR and FHR in group I and II at baseline and lowest value (P> 0.05). Onset on analgesia in group I was 9.5 minutes and in group II was 19.2 minutes. Duration of analgesia in group I was 74.1 minutes and in group II was 64.5 minutes. The difference was significant (P< 0.05). Conclusion: Combinations of ropivacaine or bupivacaine with fentanyl achieve equally effective and excellent labour analgesia.